Who are we when not ruled by others? Engaging teachers in Northern and Nordic contexts in teaching using diverse children’s literature - Strong-Wilson, Teresa; Al-Madhoun, Dina (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2026)
At a time when neoliberalism and neoconservatism would compel teachers to focus narrowly on their own contexts, we ask how crossnational conversations can break down boundaries and provide important insights for teaching to social justice. We initiate a conversation between Canada, as a Northern country, and the Nordic countries of Norway, Denmark, Sweden, Finland, and Iceland on the subject of teaching using “diverse” literature. While one main question revolves around deciding what to call the literature (multicultural? diverse? counter-story? migrant? post-colonial?), a more fundamental one centres on how to critically introduce and respond to its presence in the classroom, especially given national identities formed through Northern / Nordic exceptionalism. Imagology represents one promising direction, as does pedagogy of discomfort.